THE ANALYSIS OF BUSINESS MODEL CANVAS FOR BURGER KING INDONESIA AFFECTING CUSTOMER BUYING DECISION - Berlian Karlina (Universitas Budi Luhur, 2018)
The purpose of the study is to identify whether a business model canvas owned by Burger King Indonesia affecting consumer buying decision. The business model canvas includes the nine-elements: customer segments, value propositions, channels, customer relationship, revenue streams, key resources, key activities, key partnership, and cost structure. The analysis focusing the four model canvas: value proposition, customer segmentation, customer relationship and channel affecting consumer buying decision. Data obtained in this study were primary data get through questionnaires, and quantitatvie approach was used in this study. 100 people has become sample in this study. The analysis of the data has been performed according to conceptual framework developed from critical literature review in order to serve as a tool for deriving reliable and relevant conclusions. The results of this research are value proposition, customer segments, customer relationship have significantly and positively influence on customer buying decision. While channels have not signifcant influence on customer buying decision.